The Application of the Modular Multilevel Matrix Converter in High-Power Wind Turbines - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2016)
The trend in wind turbines has shown an ongoing power rating growth, reaching sizes up to 10 MW. Multilevel converters have therefore become a favourable solution for Multi-MW Wind Energy Conversion Systems (WECSs), due to high efficiency, reliability, controllability and the ability to reach high power/voltage ratings. Moreover, stringent grid codes to regulate the connection of WECSs to the electrical networks have been developed in countries with a high penetration of wind energy. In this context, this paper introduces the novel application of the Modular Multilevel Matrix Converter for interfacing Multi-MW Wind Turbines to provide decoupled input-output regulation, variable speed operation and fulfilment of modern grid codes. © 2016 IEEE and EPE Association.